Biomedical Technology: The transforming paradigm of Healthcare Industry with its impact on Patient Monitoring System - Kemkar, Onkar S (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Telehealth technology, which leverages wireless andenterprise networking, is changing the model of how we thinkabout going to the doctor. The ability to automatically andaccurately capture and record patient data from biomedicaldevices can improve workflow and efficiency. In this paperwe are going to discuss a patient monitoring system based onan existing industry standard communication network, usingstandard hardware components and software technologies.The standard interfaces, and flexible signal interpretationpotential.